Digital photography : the complete photographer - Ang, Tom (2016)
"Create the perfect image across 10 key photographic genres with digital photography expert Tom Ang, in this updated and newly repackaged paperback edition. Tom Ang's Digital Photography : The Complete Photographer is your ultimate guide to every style and subject of digital photography, from portraits to wildlife to architecture. Organized by genre and updated to include all the latest technological developments and creative trends, this guide is packed with practical and tailored tutorials, assignments, and advice for each of the 10 categories covered so that you can achieve the results you want -- every time."--provided by Amazon.com.
Includes index.
"Become expert in every style, from travel to fashion"--Cover.
Keywords: Photography -- Handbooks, manuals, etc; Photographers -- Biography; Photographers; Photography; Biography; Handbooks and manuals